2006
DOI: 10.1590/s0100-879x2006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Leptin is not associated independently with hypertension in Japanese-Brazilian women

Abstract: We evaluated the relationship of leptin with hypertension adjusted for body mass index (BMI) and/or waist circumference in a population of Japanese-Brazilian women aged ≥30 years with centrally distributed adiposity. After excluding diabetic subjects, the study subjects -who participated in a population-based study on the prevalence of metabolic syndrome -showed prevalence rates of obesity (BMI ≥25 kg/m 2 ) and central adiposity (waist ≥80 cm) of 32.0 and 37.8%, respectively. The hypertensive group (N = 162) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…[8][9][10][11][12]16 Among the adipocytokines an association between HT and adiponectin levels has been reported by several groups. 7,8,16,17 Although no association of adiponectin was found with BP and IR in our hypertensives, it is significantly associated with IR in controls exhibiting a physiological relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12]16 Among the adipocytokines an association between HT and adiponectin levels has been reported by several groups. 7,8,16,17 Although no association of adiponectin was found with BP and IR in our hypertensives, it is significantly associated with IR in controls exhibiting a physiological relationship.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Among the adipocytokines, leptin is a hormone which is predominantly secreted by the adipose tissue. Recent studies have shown that leptin increases arterial BP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin has been found to have strong correlation with degree of adiposity, but whether this high leptin levels contribute independently to elevated blood pressure is not known [18]. A good number of studies have observed a strong correlation between leptin and hypertension in animals as well as humans implicating leptin to have a significant contribution in the pathophysiology of obesity induced hypertension [19][20][21][22][23][24][25], however, some studies were not able to demonstrate the same results to provide an irrefutable evidence of this association [26].…”
Section: Discussionmentioning
confidence: 99%